Combination Therapy with Platelet-Rich Plasma and Epidermal Neural Crest Stem Cells Increases Treatment Efficacy in Vascular Dementia - Somayeh Akbari; Masoud Haghani; Mojtaba Ghobadi; Etrat Hooshmandi; Afshin Borhani Haghighi; Mohammad Saied Salehi; Sareh Pandamooz; Negar Azarpira; Afsoon Afshari; Shahrbanoo Zabihi; Marzieh Nemati; Mahnaz Bayat (Stem Cells International)
This study aimed to evaluate the efficacy and treatment mechanism of platelet-rich plasma (PRP) and neural crest-derived epidermal stem cells (ESCs) in their administration alone and combination in vascular dementia (VaD) model by two-vessel occlusion (2VO). Methods. Sixty-six rats were divided into six groups: the control, sham, 2VO + vehicle, 2VO + PRP, 2VO + ESC, and 2VO + ESC + PRP. The treated groups received 1 million cells on days 4, 14, and 21 with or without 500 µl PRP (twice a week) after 2VO. The memory performance and anxiety were evaluated by behavioral tests including open field, passive avoidance, and Morris water maze. The basal-synaptic transmission (BST) and long-term potentiation (LTP) were assessed through field-potential recordings of the CA1. The mRNA expression levels of IGF-1, TGF-β1, PSD-95, and GSk-3β were measured in the rat hippocampus by quantitative reverse transcription polymerase chain reaction. Results. The results demonstrated impaired learning, memory, and synaptic plasticity in the 2VO rats, along with a significant decrease in the expression of IGF-1, TGF-β1, PSD-95, and upregulation of GSK-3β. Treatment with ESC alone and ESC + PRP showed similar improvements in spatial memory and LTP induction, with associated upregulation of PSD-95 and downregulation of GSK-3β. However, only the ESC + PRP group showed recovery in BST. Furthermore, combination therapy was more effective than PRP monotherapy for LTP and memory. Conclusions. The transplantation of ESC showed better effects than PRP alone, and combination therapy increased the treatment efficacy with the recovery of BST. This finding may be a clue for the combination therapy of ESC and PRP for VaD.